2020
DOI: 10.1186/s12909-020-02130-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an audience response system on a summative assessment, a controlled field study

Abstract: Background: Audience response systems allow to activate the audience and to receive a direct feedback of participants during lectures. Modern systems do not require any proprietary hardware anymore. Students can directly respond on their smartphone. Several studies reported about a high level of satisfaction of students when audience response systems are used, however their impact on learning success is still unclear. Methods: In order to evaluate the impact of an audience response system on the learning succe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In a traditional lecture, it has been shown that the students’ attention substantially decreases after 20–25 minutes, 26 requiring an intervention such as posing lecture-based questions using ARS to get back the class’ attention. 10 Therefore, the current study, like others, found the ARS to be an efficient tool for getting enhance students’ attention. 13 , 18 , 19 This would help in providing the perceived benefit of learning and assisting students to retain their learning.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In a traditional lecture, it has been shown that the students’ attention substantially decreases after 20–25 minutes, 26 requiring an intervention such as posing lecture-based questions using ARS to get back the class’ attention. 10 Therefore, the current study, like others, found the ARS to be an efficient tool for getting enhance students’ attention. 13 , 18 , 19 This would help in providing the perceived benefit of learning and assisting students to retain their learning.…”
Section: Discussionmentioning
confidence: 52%
“…These results are in line with earlier studies that had introduced ARS in different teaching modalities like lectures, 19 case-based discussions 24 and seminars. 10 As has been seen in other studies, 8 , 19 , 24 the participation of the students also increased when ARS was introduced into anatomy and physiology lectures. This could be because the use of ARS enhanced students’ self-confidence and allowed them to gauge their abilities in comparison with their classmates.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Most commonly these devices are used for formative assessment, which is related to improved performance on summative assessment, but they can also be utilized for summative assessment. (McKenzie & Ziemann, 2020;Schmidt et al, 2020). When ARS usage is linked to a portion of the student's final grade it results in increased attendance, and increased attendance is closely linked to the final course grade (Kay & LeSage, 2009).…”
Section: Benefits/risks Of Technology In the Classroommentioning
confidence: 99%